AN ANALYSIS OF GRAMATICAL ERROR IN WRITING RECOUNT TEXT - Ilmiah Ilmiah (Elite : English and Literature Journal, 2016)
AbstractThe final project primarily deals with grammatical error analysis. This artikel aimed at finding out the grammatical error in recount text produced by the third semester students of English Department in Makassar Muhammadiyah University. The researcher used the descriptive analysis approach of which the data were obtained by the student’s recount text writing that consisted of 80 students. Than those writing were errors in producing verb groups, articles, pronouns, proposition, and conjunction. The researcher found that the students made 440 grammatical error of the Orientation, Events, and Reorientation which were classified into: 302 errors in producing verbs, 25 error of use article, 19 errors in the use of pronoun, 29 errors use of proposition, and 65 errors in the use of conjunction. It can be concluded that the students have not deep understanding in using grammatical composition in composing the next into a good structure. It is suggested that the students need more practice dealing with verb forms and tense since they were the basic knowledge needed for telling their experience.  AbstrakAnalisis Kesalahan Tata Bahasa dalam Penulisan Recount Text. Jurnal ini bertujuan untuk mengetahui kesalahan tata bahasa dalam teks recount yang dihasilkan oleh mahasiswa semester tiga Jurusan Bahasa Inggris di Makassar Universitas Muhammadiyah. Peneliti menggunakan pendekatan analisis deskriptif dimana data diperoleh dengan menulis recount teks oleh siswa yang terdiri dari 80 siswa. Kesalahan menulis yaitu dalam memproduksi kelompok kerja, artikel, kata ganti, proposisi, dan kata penghubung. Peneliti menemukan bahwa siswa membuat 440 kesalahan gramatikal orientasi, acara, dan reorientasi yang diklasifikasikan ke dalam: 302 kesalahan dalam memproduksi verba, 25 kesalahan penggunaan artikel, 19 kesalahan dalam penggunaan kata ganti, 29 kesalahan menggunakan proposisi, dan 65 kesalahan dalam penggunaan kata penghubung. Dapat disimpulkan bahwa siswa memiliki pemahaman dangkal dalam menggunakan komposisi tata bahasa dalam menyusun struktur yang baik. Disarankan bahwa siswa perlu berlatih lebih yang berkaitan dengan bentuk kata kerja karena mereka membutuhkan pengetahuan dasar untuk menceritakan pengalaman mereka.